Vitamin B6 prevents excessive inflammation by reducing accumulation of sphingosine‐1‐phosphate in a sphingosine‐1‐phosphate lyase–dependent manner. Issue 22 (23rd September 2020) - Du, Xialin; Yang, Yalong; Zhan, Xiaoxia; Huang, Yulan; Fu, Yuling; Zhang, Zelin; Liu, Honglin; Zhang, Lijie; Li, Yanfen; Wen, Qian; Zhou, Xinying; Zuo, Daming; et al.
Abstract: Vitamin B6 is necessary to maintain normal metabolism and immune response, especially the anti‐inflammatory immune response. However, the exact mechanism by which vitamin B6 plays the anti‐inflammatory role is still unclear. Here, we report a novel mechanism of preventing excessive inflammation by vitamin B6 via reduction in the accumulation of sphingosine‐1‐phosphate (S1P) in a S1P lyase (SPL)‐dependent manner in macrophages. Vitamin B6 supplementation decreased the expression of pro‐inflammatory cytokines by suppressing nuclear factor‐κB and mitogen‐activated protein kinases signalling pathways. Furthermore, vitamin B6–reduced accumulation of S1P by promoting SPL activity. The anti‐inflammatory effects of vitamin B6 were inhibited by S1P supplementation or SPL deficiency. Importantly, vitamin B6 supplementation protected mice from lethal endotoxic shock and attenuated experimental autoimmune encephalomyelitis progression. Collectively, these findings revealed a novel anti‐inflammatory mechanism of vitamin B6 and provided guidance on its clinical use.